2009
DOI: 10.1002/hed.21020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and primary tumor size on the risk for residual/recurrent well‐differentiated thyroid carcinoma

Abstract: Age, primary tumor size, and pTNM staging do not predict risk for residual/recurrent WDTC, whereas extrathyroidal extension at initial surgery is predictive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
8
24
1
1
Order By: Relevance
“…Consistent with the previous recent publications (24,25), our data also demonstrate that the AJCC staging is not the best tool for predicting the risk of recurrent/persistent disease. This is most readily apparent in the high rate of persistent/ recurrent disease seen in stage II patients.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the previous recent publications (24,25), our data also demonstrate that the AJCC staging is not the best tool for predicting the risk of recurrent/persistent disease. This is most readily apparent in the high rate of persistent/ recurrent disease seen in stage II patients.…”
Section: Discussionsupporting
confidence: 89%
“…Orlov et al [9], in a study of 246 patients, found that age, primary tumor size, and pTNM staging did not predict the risk of residual/recurrent well-differentiated thyroid cancer, whereas extrathyroidal extension at the initial surgery was a better predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the rate of persistent/recurrent disease and the disease-free status, if survival analyses were performed, represent more feasible parameters to be considered when assessing prognosis in DTC and are used as the primary endpoints in most prognostic studies about this clinical setting. Given that the AJCC/UICC system was able to predict mortality but not persistence/recurrence (Orlov et al 2009, Baek et al 2010, Tuttle et al 2010b, Vaisman et al 2012, a great effort has been made in the last decade to build novel staging systems specifically dedicated to the prediction of persistent/recurrent disease. Particularly, each of the major societies dealing with thyroid diseases (ATA (American Thyroid Association), ETA (European Thyroid Association) and LATS (Latin American Thyroid Society)) has validated a categorical classification identifying subgroups with different risks of persistent/recurrent disease (Pacini et al 2006, Pitoia et al 2009, 2013.…”
Section: Prediction Of Clinical Outcome In Differentiated Thyroid Cancermentioning
confidence: 99%